Significance of Semiquantitative Assessment of Preformed Donor-Specific Antibody Using Luminex Single Bead Assay in Living Related Liver Transplantation - Atsushi Yoshizawa; Hiroto Egawa; Kimiko Yurugi; Rie Hishida; Hiroaki Tsuji; Eiji Ashihara; Aya Miyagawa-Hayashino; Satoshi Teramukai; Taira Maekawa; Hironori Haga; Sinji Uemoto (Clinical and Developmental Immunology)
Aim. To analyze the risks of preoperatively produced donor-specific antibody (DSA) in liver transplantation. Methods. DSA was assessed using direct complement-dependent cytotoxicity (CDC) and anti-human globulin- (AHG-) CDC tests, as well as the Luminex Single Antigen assay. Among 616 patients undergoing blood type identical or compatible living donor liver transplantation (LDLT), 21 patients were positive for CDC or AHG-CDC tests, and the preserved serum from 18 patients was examined to determine targeted Class I and II antigens. The relationships between the mean fluorescence intensity (MFI) of DSA and the clinical outcomes were analyzed. Results. Patients were divided into 3 groups according to the MFI of anti-Class I DSA: high (11 patients with MFI > 10,000), low (2 patients with MFI < 10,000), and negative (5 patients) MFI groups. Six of 11 patients with high Class-I DSA showed positive Class-II DSA. Hospital death occurred in 7 patients of the high MFI group. High MFI was a significant risk factor for mortality (). Univariate analysis showed a significant correlation between MFI strength and C4d deposition (). Conclusions. HLA Class I DSA with MFI > 10,000 had a significant negative effect on the clinical outcome of patients with preformed DSA in LDLT.